2012
DOI: 10.1111/j.1398-9995.2012.02848.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of antimicrobial PLUNC proteins in nasal polyp tissues of patients with chronic rhinosinusitis

Abstract: Background-Chronic rhinosinusitis (CRS) is a disease characterized by inflammation of the nasal mucosa and paranasal sinuses. This inflammation may result in part from decreased epithelial barrier and innate immune responses, leading to frequent bacterial and fungal colonization. The objectives of this study were to investigate the expression of innate immune proteins of the Palate Lung and Nasal epithelium Clone (PLUNC) family in patients with CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 35 publications
6
93
1
1
Order By: Relevance
“…This suggests that low levels of plasminogen activators might confer an increased susceptibility to excess fibrin deposition in UT and may provide an explanation of why NP arise from mucous membranes in and around the middle nasal meatus but not in the IT. In previous studies, we have found that IT and UT differ dramatically in levels of host defense molecules, so such a regional difference is not unprecedented (36,37).…”
Section: Discussionmentioning
confidence: 86%
“…This suggests that low levels of plasminogen activators might confer an increased susceptibility to excess fibrin deposition in UT and may provide an explanation of why NP arise from mucous membranes in and around the middle nasal meatus but not in the IT. In previous studies, we have found that IT and UT differ dramatically in levels of host defense molecules, so such a regional difference is not unprecedented (36,37).…”
Section: Discussionmentioning
confidence: 86%
“…Decreased expression of some host defense molecules has been associated with CRS. 334,[519][520][521] A precise molecular pathway for this defect has not been proposed, but the cytokine IL-22 and its receptor IL-22R are key regulators of mucosal host defense, 522 acting in large part through the transcription factor STAT 3. 523,524 Diminished expression of IL-22R 525 and blunting of the STAT 3 pathway 526 have been reported; these defects appear to be associated with CRS broadly, and are not specific for the presence or absence of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies point out that SPLUNC1 has a close relationship with the inflammatory response. For example, SPLUNC1 was able to regulate Pseudomonas aeruginosa-induced lung inflammation in mice (9), and was found to be markedly downregulated in patients with chronic sinusitis (10). SPLUNC1 was found to modulate the inflammatory response to resist pulmonary inhaled particles by increasing leukocyte recruitment and phagocytic activity (11).…”
Section: Introductionmentioning
confidence: 99%